A model for using a concept inventory as a tool for students' assessment and faculty professional development. - Marbach-Ad, Gili; McAdams, Katherine C; Benson, Spencer; Briken, Volker; Cathcart, Laura; Chase, Michael; El-Sayed, Najib M; Frauwirth, Kenneth; Fredericksen, Brenda; Joseph, Sam W; Lee, Vincent; McIver, Kevin S; et al. (CBE Life Sci Educ, 2010)
This essay describes how the use of a concept inventory has enhanced professional development and curriculum reform efforts of a faculty teaching community. The Host Pathogen Interactions (HPI) teaching team is composed of research and teaching faculty with expertise in HPI who share the goal of improving the learning experience of students in nine linked undergraduate microbiology courses. To support evidence-based curriculum reform, we administered our HPI Concept Inventory as a pre- and postsurvey to approximately 400 students each year since 2006. The resulting data include student scores as well as their open-ended explanations for distractor choices. The data have enabled us to address curriculum reform goals of 1) reconciling student learning with our expectations, 2) correlating student learning with background variables, 3) understanding student learning across institutions, 4) measuring the effect of teaching techniques on student learning, and 5) demonstrating how our courses collectively form a learning progression. The analysis of the concept inventory data has anchored and deepened the team's discussions of student learning. Reading and discussing students' responses revealed the gap between our understanding and the students' understanding. We provide evidence to support the concept inventory as a tool for assessing student understanding of HPI concepts and faculty development.
Keywords: Curriculum; Faculty; Models, Theoretical; Research; Students; Teaching